Glify Majów jako najbardziej rozwinięty system pisma w Mezoameryce - Tuszyńska, Boguchwała (Scripta Neophilologica Posnaniensia, 2019)
One of the major achievements of the Maya civilization was an introduction and development of an exceptionally refined writing system. In the history of that civilization, three basic periods may be distinguished: pre-classical (2000 yBP – 250 yBP), classical (250 yBP – 900 yP), and post-classical (900 yP till the Spanish Conquest). It is especially the classical period in which a tremendous development of Maya architecture and art took place. It is also in this period that a growing number of inscriptions were produced, though the first glyphs had occurred much earlier.